The Public Value of Anthropology Engaging Critical Social Issues Through Ethnography - Tesăr, Cătălina (bu,press, 2015)
Accessible to non-specialists and researchers interested in ethnography, this volume offers an introduction into the uses of anthropology for engaging contemporary social issues. The editors' essay surveys the development of anthropological research from its early exotic, non-Western focus to today's debate over increasingly engaged approaches within a globalized society. The case studies utilize anthropology's hallmark ethnographic methodology to address issues ranging from refugee reception and recognition to fair trade, intercultural education, and encounters with Gypsy populations.